Linking of different ethnicities, races and religions to lipid profile patterns and hypolipidaemic drug usage patterns in coronary artery disease patients - Bharadwaj, Sanket P.; Patel, Aman T.; Rana, Devang A.; Malhotra, Supriya D.; Patel, Tejas M. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Coronary artery disease (CAD) is the consequence of atherosclerosis in which inadequate blood flow in the coronary arteries leads to myocardial necrosis. The impact of ethnic on CAD might be underestimated within Indian communities. There have never been any studies done associating them to lipid profile patterns in the Indian setup hence this study is the first of its kind to work towards attending the absence of data in this direction. The study aimed to evaluate the presence of ethnic differences in lipid profile patterns and hypolipidemic drug use in CAD patients. Methods: An 8-week cross-sectional prospective study was conducted in the cardiology OPD of a tertiary care hospital. Adult CAD patients prescribed with at least one hypolipidaemic drug, having their lipid profile values and willing to give informed consent were selected. The prescription pattern was noted, and the lipid profile values of the patients classified as per ATP III guidelines by NCEP. Atherogenic dyslipidaemia was considered when patients had triglyceride levels >150 mg/dl and HDL<40 mg/dl. The collected data was analyzed using SPSS. P value less than 0.05 was considered as statistically significant. Results: A total of 123 patients enrolled. Out of these, 115 were Hindus and among Hindus, most were Brahmins (34). The most prescribed hypolipidaemic drug was Rosuvastatin. Thirty six patients had high triglyceride levels out of which 35 were Hindus. Low HDL (<40 mg/dl) was present in 70 patients out of which 64 were Hindus. Atherogenic dyslipidaemia was seen in 44 patients. Majority of them belonged to the age group of 51-60 years (43.2%) and were Patels. Total cholesterol and LDL were high in 1 and 2 Jains respectively. Lipid values were higher in Tier-3 city patients. Conclusion: Hindu patients in this study showed a poorer lipid profile while among the castes, Jains and Patel’s fared poorly. It was seen that atherogenic dyslipidemia is on a rise in the Indian population.